Media and Character Education in Preventing Corruption in Indonesia: The Future Challenges - Channiago, Erin; Gomang, Jursi Hermada; Cahyani, Indah Fitri; Ginting, Fenny Tania; Isnin, Harum (Indonesia Media Law Review, 2022)
The research is aimed at providing an explanation and knowing the relationship that exists between knowledge of attitudes and moral emotions. The approach method in the research used is in the form of qualitative retrieval by managing data collected through primary data sources by means of a literature study. The data that has been collected was analyzed using descriptive analysis, focusing on the description of the meaning in several categories and correlated with the theory of character formation in order to find a correlation between the cultivation of an anti-corruptive spirit and the urgency of character education as an effort to minimize corrupt culture in Indonesia. The results of this study indicate that character education can form non-corruptive souls for the nation's generation, especially the younger generation so that they can make anti-corruption culture a culture that thickens in life and performance when they are domiciled in a state administration. The results also show that there is a relationship between knowledge attitude and moral feeling, even though the period of time is not so fast, but the impact of this moral feeling will be felt after a period of time. While in attitude behavior there is an increase in a positive direction, one of which is the implementation of the honesty canteen which in the implementation of the honesty canteen is already good with the percentage results reaching an average of 80% meaning that anti-corruption values ​​slowly begin to form with good habits which then familiarize the nation's generation to be honest and contribute greatly to the consistency of the non-corruption movement for the development of the country's progress that is free from corrupt attitudes